Legal Opinion: Legal Protection Towards Victim of Cyberbullying Case From the Perspective of Electronic Information and Transactions Law (UU ITE) - Rakheswari, Ni Made Padmawardhani (PT. Anagata Sembagi Education, 2026)
This study aims to examine the forms of cyberbullying and analyze the extent of legal protection provided to victims under Indonesian law, particularly through the Electronic Information and Transactions Law (Law No. 11 of 2008 as amended by Law No. 19 of 2016) and relevant provisions of the Indonesian Criminal Code. Using a qualitative normative–empirical approach, this research analyzes legal regulations, academic literature, and documented cases of cyberbullying to assess the effectiveness of existing legal frameworks in addressing online harassment, defamation, threats, extortion, hate speech, and cyberstalking. The findings reveal that Indonesian legislation has established comprehensive legal provisions to criminalize various forms of cyberbullying, as reflected in Articles 27, 28, and 29 of the UU ITE, as well as Articles 310 and 368 of the Criminal Code. These provisions demonstrate the government’s commitment to protecting victims; however, challenges remain in terms of legal implementation, public awareness, and the balance between law enforcement and victim protection. The study concludes that although Indonesia has made substantial efforts to regulate cyberbullying, continuous legal refinement, stronger victim-centered protection mechanisms, and enhanced digital literacy are essential to effectively address cyberbullying in the digital era.